The Effect of Teaching Modular in The Rhetorical and Retaining for Fifth Literary Stage - Zayer, Saad A. (Humanities Journal of University of Zakho, 2013)
The aim of this study is know the effect of Teaching Modular in the Rhetorical and Retaining for Fifth Literary Stage The sample of the study consisted of 152 male and female students who were distributed into two groups: one is experimental of 76 male and female students and 40 male and 36 female students; and a control group made of 40 male and 36 female students. Before the actual teaching modular, the two groups were qualified in terms of variables like: previous information test, scores of Arabic in the final examinations, parent examination, and mothers' education. The themes to be taught in the experiment were determined and the behavioral and the theme content. After that the researcher prepared a model plan to be taught in the experiments. The followers of Modular for the experimental and the traditional for the control group. The researcher prepared a test in rhetoric through which the researcher prepared has verified and applied on the two groups of the study. After data analysis by using the t-test of the two independent samples, the researcher arrived at the conclusion that there are statistical differences at the level of 0.05 for the experiment group. In the light of the result, the researcher concludes that the compxes have a positive effect in increasing the acquisition of the fifth stage students in rhetoric. The Modular help to keep the acquisition of the rhetoric. In the light of the results, the researcher recommends to design modern curricula that help to apply the technique of Modular in the secondary stage and provides the necessary devices and adopt the books and resources and the modern means of teaching. In completion to this study, the researcher recommendation that aim to know the effect of using the Modular.